2015
DOI: 10.1177/0194599815607852
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus on Head and Neck Cancer Patients Undergoing Surgery

Abstract: DM is associated with greater length of stay and hospital charges among HNCA patients. DM patients have significantly greater rates of postoperative complications, including postoperative infections, cardiac events, and acute renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 31 publications
6
40
1
1
Order By: Relevance
“…On overall multivariate logistic regression corrected for demographic factors and comorbid dyspnea and hypertension, the presence of DM remained an independent predictor of increased overall medical complications, pneumonia, unplanned reintubation, and ventilation of >48 hours. Our findings support national publications showing DM patients to be at substantially increased risk for UTI and lower respiratory tract infections . Likewise, prospective studies showed that patients who required reintubation or ventilation for >48 hours after major noncardiac surgery were significantly more likely to be diabetic .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On overall multivariate logistic regression corrected for demographic factors and comorbid dyspnea and hypertension, the presence of DM remained an independent predictor of increased overall medical complications, pneumonia, unplanned reintubation, and ventilation of >48 hours. Our findings support national publications showing DM patients to be at substantially increased risk for UTI and lower respiratory tract infections . Likewise, prospective studies showed that patients who required reintubation or ventilation for >48 hours after major noncardiac surgery were significantly more likely to be diabetic .…”
Section: Discussionsupporting
confidence: 90%
“…It has also been postulated that DM patients have decreased T‐cell–mediated immune responses and impaired neutrophil function . Furthermore, several recent studies have documented increased rates of SSI in DM patients, across multiple types of surgery, including head and neck cancer surgery . These findings held significance after controlling for various factors such as body mass index and pre‐ and postoperative hyperglycemia …”
Section: Discussionmentioning
confidence: 97%
“…Hyperglycemia have been associated with wound complications and is a risk factor for longer hospital stay and increased costs in head and neck cancer patients. 22 The degree of hyperglycemia was associated with increased myocardial infarction size in a coronary artery occlusion studies in dogs. 23 However, in this study it is not possible to gauge patients' glycemic control in the perioperative period, or recent glucose control, as evident by the hemoglobin A1c level.…”
Section: Discussionmentioning
confidence: 97%
“…Diabetes mellitus causes multiorgan dysfunction. Hyperglycemia have been associated with wound complications and is a risk factor for longer hospital stay and increased costs in head and neck cancer patients . The degree of hyperglycemia was associated with increased myocardial infarction size in a coronary artery occlusion studies in dogs .…”
Section: Discussionmentioning
confidence: 99%
“…Dabei [20,23]. Eine regelmäßige Vorsorge bei Diabetespatienten mit aktuellem oder ehemaligem Risikoprofil (starker Nikotin-oder Alkoholkonsum) scheint deshalb sinnvoll.…”
Section: Diskussionunclassified